Exosomes secreted by Blastocystis subtypes affect the expression of proinflammatory and anti-inflammatory cytokines (TNFα, IL-6, IL-10, IL-4) - Norouzi, Mojtaba; Pirestani, Majid; Arefian, Ehsan; Dalimi, Abdolhossein; Sadraei, Javid; Mirjalali, Hamed (Frontiers in Medicine, 2022)
Abstract Background: Blastocystis sp. is a common intestinal parasite, possibly responsible for diarrhea, vomiting and nausea, abdominal pain, and irritable bowel syndrome. However, many studies focused on this issue due to the uncertainty of its pathogenic potential. The extracellular vesicles (EVs) are significant mediators for cellular communication, carrying biological molecules such as proteins, lipids, and nucleic acids. Compared with other parasites, little is known about the Blastocystis EVs. Hence the present investigation was done. Methods: The Blastocystis parasites were cultured in the DMEM medium, and a 550–585 bp fragment was amplified using PCR, and sequencing was done. A commercial kit was used for exosome extraction and dynamic light scattering (DLS), flow cytometry (CD63, CD81 markers), and electron microscopy tests to determine their morphology. The human leukemia monocytic cell line (THP-1) was exposed to Blastocystis EVs. Next, the expression of proinflammatory and anti-inflammatory cytokines, including IL-4, IL-6, IL-10, and tumor necrosis factor-alpha (TNF-α), were measured using quantitative PCR. Results: Exosomes were extracted from ST1-3 Blastocystis sp. According to the DLS assay, the size of the exosomes was in the range of 30-100 nm. Electron microscopy images and CD63 and CD81 markers also confirmed the exosome's size, structure, and morphology. According to real-time PCR results, ST1-derived exosomes caused IL-6 and TNF-α upregulation and IL-10 and IL-4 downregulation, ST2- and ST3-derived exosomes downregulated IL-10, and ST3-derived exosomes caused IL-6 upregulation. There is a statistically significant difference (P-value ≤ 0.05). Conclusion: To our knowledge, this is the first report of the release of exosome-like vesicles by the human parasite, Blastocystis, and the provided information demonstrates the role of this parasite, particularly ST1 on proinflammatory and anti-inflammatory cytokines and navigating the host response. Keyword: Exosomes, Blastocystis subtypes, proinflammatory, anti-inflammatory